IMPLEMENTATION OF A FINANCIAL RECORDING SYSTEM WEBSITE BASED ON DAPOER LN MSME KUDUS - Salsabila, Zavira Raihana; Supriyati, Endang; Listyorini, Tri (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This research aims to implement a website-based financial recording system at Dapoer LN MSME Kudus, with a focus on increasing efficiency and accuracy in recording income and expenses. The system is designed to support the management of data such as income, expenses, payables, receivables, and employee data in real-time, with a simple and user-friendly interface. The implementation process uses the PHP programming language and the waterfall development method, which was chosen for its systematic linear approach so that each stage can be managed in a structured manner. The system development was performed using Visual Studio Code as the Integrated Development Environment (IDE) and MySQL as the Relational Database Management System (RDBMS). Visual Studio Code was chosen for its flexibility and extension support, while MySQL was used for its stability in handling small to medium scale data. The results of the research resulted in a website-based financial recording system that is able to manage data on income, expenses, payables, receivables, and employee data with a high level of accuracy. This system is expected to support Dapoer LN MSME Kudus in monitoring financial conditions more effectively and provide a basis for making quick and precise decisions. This article covers the entire process of designing to evaluating the system, with the hope of contributing to the increased productivity and growth of Dapoer LN MSME Kudus. In addition, this system is expected to be a reference for other MSME in improving competitiveness and operational efficiency. Thus, this research is not only beneficial for Dapoer LN MSME Kudus, but also has the potential to have a broader positive impact on the small and medium business sector. Keyword: MSME, financial, website, waterfall